PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL)SECARA DARING TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI HIDROKARBON DAN MINYAK BUMI KELAS XI MIA 2 SMA NEGERI 1 PRAFI - Zulfa Aulia (Arfak Chem: Chemistry Education Journal, 2021)
AbstractThis study aims to determine the effect (experimental class) of the Problem Based Learning learning model on the cognitive learning outcomes of students on hydrocarbons and petroleum in class XI MIA 2 SMA Negeri 1 Prafi. The sampling technique used purposive sampling and the samples obtained were class XI MIA 2 as the experimental class and class XI MIA 1 as the control class. The data collection tool is a learning outcome test. Based on the processed data obtained, the average pretest score of the experimental class was 84.23 and the average posttest of the control class was 76.37. Based on the results of the t-test hypothesis test, it was found that there was a significant effect on students' cognitive learning outcomes between the experimental class taught with the PBL learning model and the control class taught using the conventional learning model where the use of the learning model using the PBL learning model had an effect of 42%. Keywords: Learning Models, Problem Based Learning, Learning Outcomes, and Hydrocarbons